2019
DOI: 10.3390/su11082221
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of VR Application on Student’s Competency Development: A Comparative Study of Regular and VR Engineering Classes with Similar Competency Scopes

Abstract: This research focuses on the Fourth Industrial Revolution and the Korean National Competency Standards. The aim of this research is to perform a comparative study of two university engineering courses to present the difference between the effect of virtual reality (VR)-based teaching and traditional teaching on learning robotics. To achieve this goal, the authors used the expert method, focus group interviews, and a comparative study. There were three hypotheses and four research questions on the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…Nevertheless, not much study has been conducted to determine the relationship between motivation and enhanced readiness for VR training. Despite the impact of VR application on students being widely studied (Hee Lee & Shvetsova, 2019), investigating the factors for learner's readiness is important as it is believed to be essential prerequisite conditions for the effective learning process of learners (Dangol & Shrestha, 2019; Yogita & Mohammad Aslam, 2016). The current study provided an important implication on the development of practical VR training programs for medical practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, not much study has been conducted to determine the relationship between motivation and enhanced readiness for VR training. Despite the impact of VR application on students being widely studied (Hee Lee & Shvetsova, 2019), investigating the factors for learner's readiness is important as it is believed to be essential prerequisite conditions for the effective learning process of learners (Dangol & Shrestha, 2019; Yogita & Mohammad Aslam, 2016). The current study provided an important implication on the development of practical VR training programs for medical practitioners.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the student performance level analyses were mostly positive, clearly showing quantifiable increase in the students' performance levels, on multiple studies. While the majority of the studies resulted in a high level of increase in the students' performance [5]- [10], [13], others found that the VR-assisted education had no significant effect on students' performance [11], [12].…”
Section: Student Performance Evaluationmentioning
confidence: 99%
“…They may also believe that they cannot catch up with their classmates. This negative perception can affect students' selfconcepts as well as expectations for their educational attainment [11]…”
Section: Background On Hpc Developmentmentioning
confidence: 99%